Проблема противостояния «своего» и «чужого» в романе «молчание берегов» Лейлы Себбар - Лесова, Н.С. (Культура народов Причерноморья, 2013)
Современная магрибская литература сформирована на стыке двух исторических
периодов: колониальной зависимости от Франции и постколониального возрождения национальных
культур северо-африканских стран. Для этой литературы неотъемлемыми качествами являются
взаимодействие культур, использование новаторской техники письма, объединение разных
эстетических понятий. Ярким представителем магрибской литратуры и женского писательства
является алжирская романистка Лейла Себбар. Лейла Себбар интерпретирует историю родной
страны, освещая проблемы изгнанничества, поиска национальной идентичности, которая является
центральной темой ее произведений.
Ключевые слова: магрибская Сучасна магрибська література сформована на стику двох історичних періодів: колоніальної
залежності від Франції та постколоніального відродження національних культур північно-
африканських країн. Для цієї літератури невід'ємними якостями є взаємодія культур, використання
новаторської техніки письма, об'єднання різних естетичних понять. Яскравим представником
магрибської літератури й жіночого письменництва є алжирська романістка Лейла Себбар. Лейла
Себбар інтерпретує історію рідної країни, висвітлюючи проблеми вигнання, пошуку національної
ідентичності, яка є центральною темою її творів.
Ключові слова: магрибська література, колоніальна залежність, постколоніальне відродження,
національна ідентичність. Modern Maghreb literature is formed by the junction of two historical periods: the colonial rule of
France and the postcolonial revival of national cultures North African countries. Using French as a means of
expression, such well-known writers of the Maghreb, as Kateb Yacine, Mouloud Mummery, Dries Shraybi,
Mohammed Dib, Rashid Budzhedra created works that are included in the world cultural heritage.
For this literature the essential qualities are the interaction of cultures, the use of innovative writing technique,
combining different aesthetic concepts.
A good representative of the Maghreb literature and women's writing is Algerian novelist Leila Sebbar. Using
the technique of post-modernism, namely anonymous intertextuality, mythologizing art images, positioning
actions outside of space and time, the writer displays a picture of the modern post-colonial world, saturating the
narrative autobiographical elements.
Leila Sebbar interprets the history of his country, highlighting the problems of exile, the search of national
identity, which is the central theme of her works.
Key words: Maghreb literature, colonial rule, postcolonial revival, innovative writing technique, novelist, postmodernism,
anonymous intertextuality, mythologizing art images, autobiographical elements.